Comparison of conservative treatment and arthrocentesis for management of patients in Wilkes stage-3 internal derangement of temporomandibular joint - Ahmad, Junaid; Khan, Sertaj; Saeed, Sahar; Khan, Zuhaib Nasar; Inayat, Suneela; Kumar, Munesh (International Journal of Pathology, 2025)
Background: Temporomandibular joint disorders (TMDs) significantly impact oral function and quality of life, with Wilkes Stage-3 internal derangement characterized by displacement of the disc without reduction, restricted mouth opening, pain, and Mandibular deviation. The most common treatments used are conservative however; arthrocentesis has emerged as a minimally invasive alternative management option aimed at flushing out inflammatory mediators and improving joint mobility. This study evaluates the outcomes of arthrocentesis versus conservative management in patients with Wilkes Stage-3 TMD to determine their relative efficacy in the improvement of maximal mouth opening (MMO), pain reduction, and correcting mandibular deviation. Methods: A total of 84 patients were recruited in this study with a mean age: 29.71 ± 16.90 years. They were equally divided into two treatment groups: arthrocentesis (n=42) and conservative management (n=42). Statistical analysis was performed using SPSS version 26. Descriptive statistics were calculated, and paired t-tests, Wilcoxon signed-rank tests, independent t-tests, Mann-Whitney U tests, and chi-square tests were incorporated for comparisons. p-value of <0.05 was considered as statistically significant. Results: In the arthrocentesis group Improvement was observed in 70% of patients as compared to 65% in the conservative group having p=0.8445). Arthrocentesis resulted in a greater reduction in pain scores (VAS: 3.2 ± 1.1 vs. 2.6 ± 1.4, p=0.012) and a significant improvement in the deviation of mandible (2.1 ± 0.9 vs. 1.4 ± 1.2, p=0.038). However, MMO increase was not statistically significantly different between the groups (p=0.217). Conclusion: Arthrocentesis provided superior pain relief and correction of mandibular deviation as compared to conservative management, although overall improvement rates were comparable. Further research with larger sample sizes is needed.